Technical efficiency of smallholder producers in barley production in Northern Ethiopia - Enatye Moges; Endrias Geta; Tigist Mekonnen; Dubale Abate (Cogent Social Sciences, 2023)
AbstractBarley is among the major staple cereal crops in Ethiopia. Despite this, the smallholder barley producers experienced a lower level of technical efficiency due to different factors. Thus, this study is designed to estimate the level of technical efficiency and identify factors affecting the level of technical efficiency of smallholder barley producers. The data are collected from 200 randomly selected barley producers through a semi-structured questionnaire. Descriptive statistics and econometrics model are used to analyze data. The stochastic production frontier (Cobb–Douglas production function) and Tobit model were used to estimate the level of technical efficiency and identify factors affecting inefficiency, respectively. The stochastic production frontier model result revealed that there is a space to increase barley output by increasing the use of farm inputs. The mean of barley output for sample households in the 2017/18 production season was 19.5 quintals. The average level of technical efficiency of sample households was 75.1%, which implies that output can be increased by 24.9%. The frontier model indicated that labor, oxen power, fertilizer, land and seed had positive and significant effects on barley production. The Tobit model result shows that technical efficiency was affected by sex, education, livestock number, non-farm activities, credit use and non-input total expenditure. This shows that there is a room to increase technical efficiency of barley production in the study area. Therefore, appropriate policies and strategies directed towards the above-mentioned significant variable should be designed to improve the productivity of barley in the study area.